2014
DOI: 10.2458/56.16936
|View full text |Cite
|
Sign up to set email alerts
|

Direct Radiocarbon Dating of Late Pleistocene Hominids in Eurasia: Current Status, Problems, and Perspectives

Abstract: The corpus of radiocarbon dates run directly on Pleistocene-age human remains in Eurasia (∼120 values, with ∼80 of them found to be reliable) is analyzed and interpreted. The latest Neanderthals are dated to ∼34,000–30,500 BP (∼38,800–35,400 cal BP). They probably coexisted with the first modern humans at ∼36,200–30,200 BP (∼42,500–32,800 cal BP) in the western and central parts of Europe. The earliest direct 14C dates on modern humans in Eurasia are ∼34,950–33,300 BP (∼40,400–37,800 cal BP). A paucity of 14C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 77 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Several studies, however, including radiocarbon dating of Palaeolithic humans (e.g. Kostenki 1; see Kuzmin & Keates 2014), have shown that there are no significant discrepancies between the radiocarbon values obtained from either non-UF or UF collagen. Moreover, although it is suggested that the dating of SAA, mainly hydroxyproline (Hyp), is reliable because this compound is assumed to be “almost only ever naturally found in mammalian collagen” (Reynolds et al 2017: 1441), this is not exactly true.…”
Section: Which Of the Bone Dating Materials Is The Most Reliable?mentioning
confidence: 99%
“…Several studies, however, including radiocarbon dating of Palaeolithic humans (e.g. Kostenki 1; see Kuzmin & Keates 2014), have shown that there are no significant discrepancies between the radiocarbon values obtained from either non-UF or UF collagen. Moreover, although it is suggested that the dating of SAA, mainly hydroxyproline (Hyp), is reliable because this compound is assumed to be “almost only ever naturally found in mammalian collagen” (Reynolds et al 2017: 1441), this is not exactly true.…”
Section: Which Of the Bone Dating Materials Is The Most Reliable?mentioning
confidence: 99%
“…bone and teeth) and their associated tools (i.e. ivory, bone or antler), progress in sample pretreatments using ultrafiltration 22 , have led to the redating of samples initially dated during the eighties and nineties 23 27 . However, ultrafiltration is often associated with lower extraction yields (especially when bones are moderately to poorly preserved), and does not always allow for the recovery of a sufficient amount of collagen when sample mass is lower than 100 mg. As a result, all previous attempts have failed 23 , 24 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Another fossil curated at the Musée de l'Homme is the individual THS 10 found at Tam Hang South by Fromaget. Thanks to the same program, THS 10 was dated to 15,740 ± 80 B P which represents an unresolved stratigraphic incongruity as i) Bacon (2012) reported a maximum age of 13,215 B P at 3.25 m and ii) Fromaget and Saurin (1936) clearly indicated that the Tam Hang South excavation was stopped at 1.60 m. A similar incongruity concerns the paleoanthropological remains recently uncovered from the neighbouring cave Tam P'a Ling, as pointed out by Pierret et al (2012) and discussed further by Kuzmin and Keates (2014). The intrusive position of TPL1 modern human remains direct-dated to 63.6 ka in sediment dated between 46 ka (OSL) and 2.77 ka (AMS 14 C) still awaits a convincing depositional explanation (Fig.…”
Section: Old Human Remains In Laosmentioning
confidence: 90%